Levels of Value Integration in Federal Agencies' Mission and Value Statements: Is Open Government a Performance Target of U.S. Federal Agencies?. (25th March 2018) - Piotrowski, Suzanne; Rosenbloom, David H.; Kang, Sinah; Ingrams, Alex
Abstract: The Barack Obama administration advanced open government initiatives to make federal administration more open, accountable, and responsive to citizens. Yet a question remains whether federal administrators took notice. This article examines changes in the extent to which U.S. federal agencies have integrated the three core principles of open government—transparency, public participation, and collaboration—into their performance planning. By analyzing 337 annual performance plans of 24 major federal agencies from fiscal years 2001 to 2016, the authors found that, overall, the level of integration of open government into performance planning has been trending higher since the early 2000s. During the Obama presidency, integration initially rose sharply but later declined. Findings also show that agencies' stated core values regarding open government are not consistently integrated into their performance plans. The implications of these findings for incorporating democratic‐constitutional values into holistic performance management are considered .